PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ONLINE NOVRETTA SHOP DI SHOPEE INDONESIA - Sapri; Subagiyo; Ilyas, Meifida (Jurnal Satya Mandiri Manajemen dan Bisnis, 2023)
This study aims to produce information in the form of a more in-depth explanation of the Effect of Quality, Price and Promotion on Purchasing Decisions (At the Novretta Shop Online Store at Shopee Indonesia). The method used in this research is descriptive and verification with a population and sample of 95 respondents, data processing using the SPSS Version 25 application. It is known that the calculated F value is 23.048> F table of 2.70 with a significant level of 0.00 <0.05. This proves that there is a significant influence between the variables of product quality, price and promotion on purchasing decisions or simultaneously (together) between the variables of product quality, price and promotion have a significant effect on purchasing decisions, so that H0 is rejected and H4 is accepted. It is known that the t value for product quality (X1) is the t value greater than the t table (2.907> 1.98638) and the value of the significant level is below 0.05, namely 0.005. Meanwhile, for the price variable (X2), the t value is smaller than the t table (1.553 < 1.98638) and the value of the significant level above 0.05 is 0.124, while for the promotion variable (X3), the t value is greater than the t table (5.958> 1.98638) and the value of the significant level below 0.05 is 0.000. The coefficient of determination (R2) that the contribution of product quality, price and promotion variables to the purchasing decision variable is 0.413 or 41.3% and the remaining 58.7% is influenced by other factors not examined in this analysis.